Mechanism by which Eucommia ulmoides leaves Regulate Nonalcoholic fatty liver disease based on system pharmacology. (10th January 2022) - Gong, Man; Su, Chengfu; Fan, Mengzhe; Wang, Ping; Cui, Bingdi; Guo, Zhongyuan; Liang, Shaojia; Yang, Lianhe; Liu, Xiaoqian; Dai, Liping; Wang, Zhimin
Abstract: Ethnopharmacological relevance: Eucommia ulmoides ( E. ulmoides ) leaves are included in the Chinese Pharmacopoeia, and are traditionally used to treat hypertension, obesity, diabetes, and other diseases. Numerous pharmacological studies have shown that E. ulmoides has a good effect on lowering blood lipids and can improve obesity and nonalcoholic fatty liver. Aim: To study the mechanism of E. ulmoides leaves in regulating nonalcoholic fatty liver disease by combining prediction and validation. Methods: Using network pharmacology, and molecular docking to predict E. ulmoides in regulating the action mechanism and potential active ingredients of nonalcoholic fatty liver, large hole adsorption resin enrichment active sites, in vitro experiments were performed to verify its fat-lowering effect and mechanism. Results: The major components of E. ulmoides leaves exhibited good combination with lipid metabolism-regulating core proteins, particularly flavonoids. EUL 50 significantly reduced lipid accumulation, and increased PPARγ. Compared with the control group, the autophagy level increased after the administration of EUL 50. PPARγ decreased significantly after the addition of chloroquine (CQ, autophagy inhibitor). Conclusion: The active ingredients in E. ulmoides leaves regulating nonalcoholic fatty liver disease are mainly flavonoids and phenolics. EUL 50 may play a role in lowering lipids by regulating PPARγ expression through inducing autophagy. Graphical abstract: Image 1